Analisis Kebutuhan Kamus Baca Bergambar untuk Mempermudah Siswa Belajar Bahasa Mandarin - Prabawati, Chintya; Anggraeni, Anggraeni (Universitas Negeri Semarang, 2020)
Kamus baca bergambar merupakan salah satu media penunjang pembelajaran yang dapat membuat siswa lebih tertarik dan mempermudah dalam proses pembelajaran. Berdasarkan observasi, bahwa banyak berbagai macam kamus baca bergambar yang ditemukan. Hal ini dapat mempengaruhi daya tangkap pemahaman siswa dalam Bahasa Mandarin. Oleh sebab itu, pada penelitian iniÃ‚Â peneliti berusaha menganalisis kamus baca bergambar Bahasa Mandarin sesuai dengan kebutuhan siswa. Tujuan penelitian ini, yaitu 1) Mengetahui kebutuhan siswa akan kamus baca bergambar untuk mempermudah siswa dan guru belajar bahasa Mandarin, 2) Mengetahui kesesuaian kamus baca bergambar dengan kebutuhan siswa melalui analisis SWOT untuk mempermudah belajar bahasa Mandarin. Penelitian ini menggunakan metode deskriptif kualitatif, karena peneliti akan menjabarkan kebutuhan kamus baca bergambar untuk mempermudah siswa belajar Bahasa Mandarin. Hasil dari penelitian ini menghendaki kamus baca bergambar yang sesuai dengan kebutuhan siswa berdasarkan penyusunan kosakata, jumlah kosakata per halaman, tampilan/ layout kosakata, font Hanzi, font size Hanzi, font Pinyin, font size Pinyin, gambar/ ilustrasi.Picture reading dictionary is one of the supporting learning media that can make students more interested and simplify the learning process. Based on observations, that many various kinds of picture reading dictionaries were found. This can affect the comprehension of students' comprehension in Mandarin. Therefore, in this study the researchers tried to analyze the Chinese picture reading dictionary according to the students' needs. The purpose of this study, namely 1) Knowing the needs of students for picture reading dictionaries to facilitate students and teachers learning Mandarin, 2) Knowing the suitability of picture reading dictionaries with students' needs through SWOT analysis to facilitate learning Chinese. This research uses descriptive qualitative method, because the researcher will describe the need forÃ‚Â a picture reading dictionary to facilitate students learning Mandarin. The results ofÃ‚Â this study require a picture reading dictionary that suits students' needs based on vocabulary preparation, number of vocabularies per page, display / layout of vocabulary, Hanzi fonts, Hanzi font sizes, Pinyin fonts, Pinyin font sizes, pictures / illustrations.Picture reading dictionary is one of the supporting learning media that can make students more interested and simplify the learning process. Based on observations, that many various kinds of picture reading dictionaries were found. This can affect the comprehension of students' comprehension in Mandarin. Therefore, in this study the researchers tried to analyze the Chinese picture reading dictionary according to the students' needs. The purpose of this study, namely 1) Knowing the needs of students for picture reading dictionaries to facilitate students and teachers learning Mandarin, 2) Knowing the suitability of picture reading dictionaries with students' needs through SWOT analysis to facilitate learning Chinese. This research uses descriptive qualitative method, because the researcher will describe the need forÃ‚Â a picture reading dictionary to facilitate students learning Mandarin. The results ofÃ‚Â this study require a picture reading dictionary that suits students' needs based on vocabulary preparation, number of vocabularies per page, display / layout of vocabulary, Hanzi fonts, Hanzi font sizes, Pinyin fonts, Pinyin font sizes, pictures / illustrations.